Overweight Increases the Risk of Right Ventricular Dysfunction in the non-Breastfed Infants - Bishr, Nehad Taha; Darweesh, Mohamed S.; G. Amer, Eman; Abul-Fadl, Azza M.A.; Al-Jawaldeh, Ayoub (International Journal of Scientific Research and Management (IJSRM), 2020)
Background: Overweight in infancy could increase the risk of cardiovascular disease (CVD) and diabetes mellitus (DM) in later life, however the mechanisms are need to be investigated.Aim: To assess the relationship between overweight and right ventricular function during infancy in relation to the mode of feeding.Methods: A cross-sectional study was conducted for 76 healthy infants aged 3 to 12 months of life (38 breastfed (BF) and 38 milk formula fed (MFF). Anthropometric measurements were done for weight, supine length and body mass index (BMI). The right ventricular functions (RV) were assessed by two dimensional (2D) echocardiography and Tissue Doppler Imaging (TDI).Results: BMI percentiles were significantly higher in MFF infants compared to BF infants (P